Diversity, Biomass Accumulation and Carbon Storage of Shrub Community in a Foothill Forest of Indian Eastern Himalayas - Shukla, Gopal; Abha Manohar, K.; Rai, Prakash; Chakravarty, Sumit (Indian Forester, 2019)
Understorey vegetation especially the shrub is a dynamic layer of the forest strata. Shrub communities are very useful for protecting the soil and water regimes and improves productivity and soil fertility. However, as compared to trees, studies on shrub diversity and ecology still remains neglected. Thus, a study was carried out at sub-humid tropical foothill forest of West Bengal, India to document the status of shrub diversity, biomass and carbon accumulation. Quantitative characters were analyzed with help of random quadrate sampling method. Species richness of the shrubs in the forest was thirty two. The shrub diversity index, concentration of dominance, Shannon and Wiener index and evenness index was estimated as 0.73, 0.037, 2.87 and 1.89, respectively. Relative frequency varied from 0.22 to 2.00. Density ranged from 0.84 to 456.11 individuals ha-1 and relative density ranged from 0.08 to 1.25 %. Relative abundance ranged from 0.14 to 1.79 %. IVI values ranged from 0.47 to 3.71. This indicates the the shrub communities in the forest diverse but dominance distributed with less skewed IVI values. Biomass and carbon storage of shrub communities in the forest was 4.90 and 2.21 Mg ha-1, respectively. Stems contributed the most to the total shrub biomass and carbon storage.